Missed scaphoid fracture: Diagnostic difficulty and treatment dilemma. - KC, Kapil Mani; GC, Raju (Nepal Orthopaedic Association Journal, 2023)
Scaphoid is the most common carpal bone to be fractured, accounting for approximately 15% of all wrist fractures. Most important aspect in managing such fractures is the inability to achieve accurate diagnosis, especially when these fractures are undisplaced, minimally displaced, or occult in nature. There is a lack of knowledge regarding such injuries among first responders, especially at primary and secondary care set up of our country. Majority of such injuries are missed in initial evaluation and result in scaphoid non-union, which are difficult to manage and result in functional disability. Detailed physical examination, including, anatomical snuff box tenderness, volar distal tuberosity tenderness, or positive scaphoid compression test (sensitivity 70.5% and specificity 21.8%) along with appropriate radiographic assessment are essential to reach the correct diagnosis and commence the treatment early. The aim of this study is to highlight the challenges and discuss the potential solutions in managing patients with occult scaphoid fractures